2014
DOI: 10.1186/1471-2164-15-s9-s4
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequence and analysis of the Marwari horse breed and its genetic origin

Abstract: BackgroundThe horse (Equus ferus caballus) is one of the earliest domesticated species and has played an important role in the development of human societies over the past 5,000 years. In this study, we characterized the genome of the Marwari horse, a rare breed with unique phenotypic characteristics, including inwardly turned ear tips. It is thought to have originated from the crossbreeding of local Indian ponies with Arabian horses beginning in the 12th century.ResultsWe generated 101 Gb (~30 × coverage) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…Similar to most previous studies [ 34 , 35 ], we consistently observed a higher SNV frequency in intergenic rather than genic regions for all species. As shown in Figure 2 , 34.23~36.31% of total SNVs were genic variants, including 0.60~0.69% that were in exons.…”
Section: Resultssupporting
confidence: 91%
“…Similar to most previous studies [ 34 , 35 ], we consistently observed a higher SNV frequency in intergenic rather than genic regions for all species. As shown in Figure 2 , 34.23~36.31% of total SNVs were genic variants, including 0.60~0.69% that were in exons.…”
Section: Resultssupporting
confidence: 91%
“…In our study, the average number of CNVs per individual was 96, ranging from 88 to 108, significantly fewer than the number identified by Jun et al . (; 353/1; NGS) and Doan et al . (2012b; 282/1; NGS) and slightly fewer than identified by Doan et al .…”
Section: Resultsmentioning
confidence: 99%
“…The clean reads were aligned to the reference genome of E. caballus, which is the most accurate and commonly used reference genome for horses [23,24], using TopHat v2.0.12 ( Table 2). In total, 84.85% (BSM1), 85.05% (BSM2), 84.25% (BSM3), 84.38% (ASM1), 84.14% (ASM2), and 84.23% (ASM3) clean reads were uniquely mapped to the reference genome.…”
Section: Mrna Expression Profiles In Mongolian Horse Testis Developmentmentioning
confidence: 99%